Multifunctional structural supercapacitors for electrical energy storage applications. (May 2014) - Javaid, A; Ho, KKC; Bismarck, A; Shaffer, MSP; Steinke, JHG; Greenhalgh, ES
A novel concept of structural supercapacitors based on carbon fibre-reinforced composites has been introduced that can simultaneously act as a structural component and an electrical energy storing device. Supercapacitors consisting of woven carbon fibre mat electrodes; filter paper insulator and crosslinked poly(ethylene glycol) diglycidylether/diglycidylether of bisphenol-A polymer electrolytes were fabricated. Brunauer–Emmett–Teller surface area analysis and tensile tests were conducted on the as-received and activated carbon fibre reinforcements. Compression tests and ionic conductivity measurements were conducted on the polymer electrolytes while charge/discharge electrochemical tests and shear testing were done on the structural supercapacitors. This was to investigate the implications of increased diglycidylether of bisphenol-A loading in crosslinked poly(ethylene glycol) diglycidylether polymer electrolytes and carbon fibre activation on the multifunctionality of structural supercapacitors. The addition of diglycidylether of bisphenol-A increased the compressive stiffness, although the ionic conductivity was compromised. Specific capacitance of the structural supercapacitors was increased with the chemical activation of carbon fibre electrodes. Carbon fibre activation led to improved specific capacitance of the structural supercapacitors and the addition of diglycidylether of bisphenol-A increased the shear modulus, although the specific capacitance was compromised.